Aryl hydrocarbon Receptor activation during in vitro and in vivo digestion of raw and cooked broccoli (brassica oleracea var. Italica). Issue 5 (23rd April 2020) - Koper, Jonna E. B.; Kortekaas, Maaike; Loonen, Linda M. P.; Huang, Zhan; Wells, Jerry M.; Gill, Chris I. R.; Pourshahidi, L. Kirsty; McDougall, Gordon; Rowland, Ian; Pereira-Caro, Gema; Fogliano, Vincenzo; Capuano, Edoardo
Abstract : Glucosinolates in broccoli can be converted upon chewing and processing into Aryl hydrocarbon Receptor (Ahr) ligands. Abstract : Broccoli is rich in glucosinolates, which can be converted upon chewing and processing into Aryl hydrocarbon Receptor (AhR) ligands. Activation of AhR plays an important role in overall gut homeostasis but the role of broccoli processing on the generation of AhR ligands is still largely unknown. In this study, the effects of temperature, cooking method (steaming versus boiling), gastric pH and further digestion of broccoli on AhR activation were investigated in vitro and in ileostomy subjects. For the in vitro study, raw, steamed ( t = 3 min and t = 6 min) and boiled ( t = 3 min and t = 6 min) broccoli were digested in vitro with different gastric pH. In the in vivo ileostomy study, 8 subjects received a broccoli soup or a broccoli soup plus an exogenous myrosinase source. AhR activation was measured in both in vitro and in vivo samples by using HepG2-Lucia™ AhR reporter cells. Cooking broccoli reduced the AhR activation measured after gastric digestion in vitro, but no effect of gastric pH was found. Indole AhR ligands were not detected or detected at very low levels both after intestinal in vitro digestion and in the ileostomy patient samples, which resulted in no AhR activation. This suggests that the evaluation of the relevance of glucosinolates for AhR modulation in the gut cannot prescind from the way broccoli is processed, and that broccoli consumption does not necessarily produce substantial amounts of AhR ligands in the large intestine.